Didactic conceptions and use of ICT in the university education of degree. Multi-case study and TPACK analysis framework (Praxis Educativa, 2018)
We present partial results of the research “The construction of didactic knowledge of content in experienced and beginners teachers of the UNNE. Multi-case study”,whose objective is the understanding of the processes of construction of the professional knowledge of university teachers, specifically related to the didactic- echnological knowledge of the content (TPACK). We propose the analysis of  eachers’ representations on the use of ICTs in teaching proposals and in student  earning experiences, central aspects to locate the technological dimension in different levels  of curricular integration in the aulic projects. We report 4 case studies consisting of  arratives of experienced teachers of single-paradigmatic and multiparadigmatic  disciplines of two Academic Units of the UNNE. Based on the analysis and  interpretation of the different modes of integration of digital technologies, we note the emergence of indications that account for the complex relationships between didactic,  technological and disciplinary knowledge.
Keywords: ICT curriculum integration; experienced university professors; representations around ICT